The Development of Top 200 Prescribed Drugs in Community Pharmacies at Medan City as a Learning Tools - Tanjung, Hari Ronaldo; Nasution, Embun Suci (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The pharmacy student at clerk-ship level and pharmacists need the drug information literature contains information of prescribed drug that utilized in pharmaceutical practice daily in order to learn effectively. The aims of the study was to develop top 200 prescribed drugs in community pharmacies at Medan city as a learning tools for the pharmacy students at clerk-ship level and pharmacists. Methods: The study was a descriptive study that used a cross sectional survey methodology. The top 200 items of prescribed drugs obtained from the pharmacies selected regarding to random sampling method. The study was conducted from August to November 2016. The top 200 prescribed drugs lists was developed in to a draft of drug information book and a group of pharmacy students at clerk-ship level and pharmacists was asked to evaluate the book and gave suggestions using a set ofÂ  questionnaire. Results: The top 200 prescribed drugs list revealed that the five most prescribed drugs was amoxicilline (5.55 %), followed by dexamethasone (4.44%), mefenamic acid (3.73%), cetirizine (3.16%), and ciprofloxacine (2.97%). The result of a draft of drugs information book evaluation that was evaluated by 120 pharmacy students and pharmacists showed the drug information book draft was good and able to publish. The respondents mention some suggestion for the book i.e. Â Image made more attractive and in various colors and the image adjusted with an indication of drugâ€ (43.74%) and Using language that is easily understood and more detailed informationâ€ (16.85%). Conclusions: The study has developed top 200 prescribed drugs in community pharmacies at Medan city in to a validated drug information book as a learning tool. The drug information book very useful for a continuing professional development program for pharmacists and build the pharmacy student's confidence before they face the real patients at the community pharmacy practice setting. Key words: Prescribed drugs, drug information, learning tools